Temporal turnover of the soil microbiome composition is guild-specific - Martinović, Tijana; Odriozola, Iñaki; Mašínová, Tereza; Doreen Bahnmann, Barbara; Kohout, Petr; Sedlák, Petr; Merunková, Kristina; Větrovský, Tomáš; Tomšovský, Michal; Ovaskainen, Otso; Baldrian, Petr (Ecology letters, 2021)
Although spatial and temporal variation are both important components structuring microbial communities, the exact quantification of temporal turnover rates of fungi and bacteria has not been performed to date. In this study, we utilised repeated resampling of bacterial and fungal communities at specific locations across multiple years to describe their patterns and rates of temporal turnover. Our results show that microbial communities undergo temporal change at a rate of 0.010-0.025 per year (in units of Sorensen similarity), and the change in soil is slightly faster in fungi than in bacteria, with bacterial communities changing more rapidly in litter than soil. Importantly, temporal development differs across fungal guilds and bacterial phyla with different ecologies. While some microbial guilds show consistent responses across regional locations, others show site-specific development with weak general patterns. These results indicate that guild-level resolution is important for understanding microbial community assembly, dynamics and responses to environmental factors.
Keywords: mikrobiota; temporal turnover; bacteria; soil; Fungi; Mycobiome; půdní mikrobiologie; houby; forest; fungi; mykobiom; půda; Soil Microbiology; community assembly; Microbiota; Soil